Do Migrants Pay Their Way? A Net Fiscal Analysis for Germany - Hend Sallam; Michael Christl (Global Labor Organization (GLO), 2024)
This study quantifies the direct average net fiscal impact (ANFI) of migration in Germany, taking into account both indirect taxes and in-kind benefits such as health and education spending. Using a status quo approach with data from the German Socio-Economic Panel (SOEP) for 2018 and microsimulation techniques to impute both indirect taxes and in-kind benefits, our results show that migrants, especially first-generation migrants, have a more favorable net fiscal impact on average compared to natives. However, we demonstrate that this result is mainly driven by the favourable age structure of migrants. When controlling for demographic differences between these groups, we show that second-generation migrants contribute very similarly to natives to the German welfare state. Nevertheless, both natives and second-generation migrants, respectively, contribute more than first-generation migrants. These differences persist even when we do not account for indirect taxes and benefits-in-kind.
Keywords: F22; H24; H50; 330; immigration; net fiscal impact; public finances; tax-benefit system